An improvement of architectural firm management in adopting green design criteria - Samari, Milad (2016)
Among the vanous industries which have negative impact on the environment, construction industry is the one receiving most attention. Thi is because it had long been perceived as the cause of destruction of natural environment. Thus, industrial experts and researchers have put their efforts into reducing the negative impact of construction activities through green design criteria (GDC). Green design concern with reducing environmental impacts that could lead to itnprovement of energy efficiency, and occupancy sati faction. The previou studies indicate that the de ign phase is crucial becau e mo t of the con truction methods, setting, and materials are detetmined during this phase. Therefore architectural firm , which are the major actors in the de ign and con truction phases, can play essential roles in improving environmental performance in the entire construction process by applying GDC.